CMOS-compatible synaptic transistor gated by chitosan electrolyte-Ta2O5 hybrid electric double layer - Shin-Yi Min (Nature Portfolio, 2020)
Abstract This study proposes a hybrid electric double layer (EDL) with complementary metal-oxide semiconductor (CMOS) process compatibility by stacking a chitosan electrolyte and a Ta2O5 high-k dielectric thin film. Bio-inspired synaptic transistors with excellent electrical stability were fabricated using the proposed hybrid EDL for the gate dielectric layer. The Ta2O5 high-k dielectric layer with high chemical resistance, thermal stability, and mechanical strength enables CMOS-compatible patterning processes on biocompatible organic polymer chitosan electrolytes. This technique achieved ion-conduction from the chitosan electrolyte to the In-Ga-Zn oxide (IGZO) channel layer. The on/off current ratio, subthreshold voltage swing, and the field-effect mobility of the fabricated IGZO EDL transistors (EDLTs) exhibited excellent electrical properties of 1.80 × 107, 96 mV/dec, and 3.73 cm2/V·s, respectively. A resistor-loaded inverter was constructed by connecting an IGZO EDLT with a load resistor (400 MΩ) in series. This demonstrated good inverter action and responded to the square-wave input signals. Synaptic behaviours such as the hysteresis window and excitatory post-synaptic current (EPSC) variations were evaluated for different DC gate voltage sweep ranges and different AC gate spike stimuli, respectively. Therefore, the proposed organic–inorganic hybrid EDL is expected to be useful for implementing an extremely compact neural architecture system.